THE EFFECT OF THINK PAIR SHARE TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN SPEAKING - Dessy Putri Utami; Sumarsih Sumarsih (Universitas Negeri Medan, 2015)
This study aims to find out whether students’ achievement taught by using Think Pair Share Technique has significant effect than taught Dictation Technique in Speaking. The research was conducted by Experimental research using in two groups. They are experimental used Think Pair Share Technique and Control used Dictation Technique. The subject of this were the students of SMAN 6 Medan class X-2 and X-3 consisted of 38 students for each class. The data was taken from Speaking test. After analyzing the data, it was found that the value of t-obs was 3.982 with degree of freedom (df) 38 at the level of significance p (0.05) = 2.024. It means that t-obs is higher than t-table. It was found that students achievement in Speaking taught by Think Pair Share Technique has significant effect than Dictation Technique. Keywords : Think Pair Share, Speaking Achievement, Dictation